2006
DOI: 10.1007/s00264-006-0087-x
|View full text |Cite
|
Sign up to set email alerts
|

P-15 small peptide bone graft substitute in the treatment of non-unions and delayed union. A pilot clinical trial

Abstract: Treatment of non-unions and delayed unions often requires osteogenic material. Recently, a biomimetic bone matrix that simulates the cellular environment of hard tissue, identified as P-15, was introduced to the orthopaedic community. A total of 22 patients with mal-union or delayed union fractures was treated from June 2000 to October 2003 with P15- bone graft substitute (P15-BGS) in the site of fracture and mostly with internal fixation. Patients were examined by independent radiographic analysis. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…Furthermore, the 9.0 ± 7.3% of residual ABM/P-15 revealed by histomorphometry may have continued to form new bone in vivo and added to the percentage of new bone formation, thus making the difference between the mean scores of the treatments even smaller with additional time (Table 3). The successful bone formation results achieved in this study with ABM/P-15 are consistent with results obtained in other preclinical models [14][15][16], dental models [17][18][19][20][21][22][23][24][25][26], and the pilot orthopaedic model [9].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the 9.0 ± 7.3% of residual ABM/P-15 revealed by histomorphometry may have continued to form new bone in vivo and added to the percentage of new bone formation, thus making the difference between the mean scores of the treatments even smaller with additional time (Table 3). The successful bone formation results achieved in this study with ABM/P-15 are consistent with results obtained in other preclinical models [14][15][16], dental models [17][18][19][20][21][22][23][24][25][26], and the pilot orthopaedic model [9].…”
Section: Discussionsupporting
confidence: 89%
“…A pilot study by Gomar et al [9] used ABM/P-15 as a bone graft substitute to treat delayed or non-unions in various long bones in adult trauma. The study reported full consolidation in 90% of patients (20 of 22) at an average of 4.2 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 P15/ABM TM (Cerapedics, Westminster, CO) has also been used clinically and shown to improve osteointegration in spinal fusion studies. [13][14][15] Numerous attempts to improve osteointegration of Ti implants have been attempted with varying degrees of success. 16,17 Recent attention has been focused on the immobilization of small bioactive molecules on the implant surface.…”
mentioning
confidence: 99%